Qualitative Study: Family Planning Village Program Development to Increase Community Health Improvement in Banyuwangi Regency - Jayanti Dian Eka Sari; Syifa’ul Lailiyah; Diansanto Prayoga; Mohammad Zainal Fatah; Ajeng Febrianti Rahayu (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Family Planning Village is one of the strategic innovations that has been implemented by the BKKBN since 2015. However, its implementation remains not optimal during the 4 years of the program. The purpose of this study was to analyze the FP Village program in improving the community health status in Banyuwangi Regency. This was a quasi-experimental study with a qualitative approach. The research was carried out in two villages that have a FP Village program in Banyuwangi Regency, consisting of FP Village representatives located in the urban areas and suburban areas of Banyuwangi, starting from July to November 2019. Data was collected using literature study, in-depth interview, and FGDs. Based on the result of the study, the implementation scope of the FP Village program in Wringinagung and Gambiran was in accordance with the 2015 FP Village program technical manual. The development of the FP Village program can be done by making edutourism and utilizing local potential in the program implementation.